INTERNALISASI MODERASI BERAGAMA DALAM STANDAR KOMPETENSI KEMANDIRIAN PESERTA DIDIK - Rifqi Muhammad (Jurnal Ilmiah Al-Muttaqin, 2021)
The purpose of this study was to describe the internalization of religious moderation in the Student Independence Standards (SKKPD) in higher education. This study uses a qualitative approach with the type of library research research. Primary data sources are documents related to religious moderation and students' independent competency standards. The analysis of research data is inductive which consists of reduction, category, synthesis and preparation of working hypotheses. The results showed that the internalization of the dimensions of religious moderation in the standard of competence for independence of students, namely: by making religious moderation an aspect of the development of the foundation of life for religious moderation; 1) Examine deeper into the meaning of the National Commitment; Tolerance; Anti violence; and accommodating to local culture; 2) Living up to the values ​​of the National Commitment; Tolerance; Anti violence; and accommodating to local culture; 3) Sincerity in carrying out the National Commitment; Tolerance; Anti violence; and accommodating to local culture